Intraductal papillary neoplasm of the bile duct - Pierini, Ángel; Pierini, Leandro; Ruiz, Guillermo; Evans Rhys, Brian; Elias, Juan Pablo; Meneghini, Rodrigo (Cirugía del Uruguay, 2022)
Papillary intraductal neoplasia of the bile duct (NPIVB) is a rare entity characterized by exophytic papillary growth of the biliary epithelium towards the ductal lumen. Previously included in the group of tumors of the same name in pancreatic location, it presents obvious differences with them and since 2010 it has been considered a separate entity with demonstrated potential for malignancy towards cholangiocarcinoma